Answers

2015-10-30T23:40:39+05:30
ATQ :-

A + B = 2x-2 ------(1)

A - B = 4x-8 -------(2)

Adding (1) & (2)

2A = 2x - 2 + 4x - 8

2A = 6x - 10

A = 6x-10/2


Putting A in any eqn.

6x - 10 / 2 + B = 2x - 2

B = (2x - 2 ) - ( 6x-10/2)

B = 10x + 6 / 2
0
2015-10-31T00:09:18+05:30
we know that,
A + B = 2x - 2 ......(i)
A - B = 4x - 8 .......(ii)
on adding both the eq. (i) and (ii) we get
A + B = 2x - 2 
A - B = 4x - 8
2A = 6x - 10
A = (6x - 10) / 2
A = 2(3x - 5) / 2
A = 3x - 5

Now, Substituting the value of A = 3x - 5 in  eq  (i), we get
A + B = 2x - 2 
3x - 5 + B = 2x - 2 
B = 2x - 2 - (3x - 5)
B = 2x - 2 - 3x + 5
B =  -x + 3
B = 3 - x

0